Reviving the Discussion on the Rationale Underlying the Comparison Question Test. Issue 2 (October 2014) - Elaad, Eitan
There has been a long-standing debate around the rationale underlying the Comparison Question Test, which assumes that guilty suspects will have consistently larger responses to crime-related (relevant) than to general emotional (comparison) questions, whereas innocent suspects will show the opposite pattern of responding. This debate largely came to a close when the National Research Academy (2003) concluded that "The theoretical rationale for the polygraph is quite weak, especially in terms of differential fear, arousal, or other emotional states that are triggered in response to relevant or comparison questions" (p. 213). A recent study provides new insight into the test's logic and may restart a discussion about, the nature of the test.